KONTRIBUSI IRAN TERHADAP SEJARAH PEMBAHARUAN HUKUM KELUARGA ISLAM: Potret Sistem Kewarisan Islam dan Wasiat Wajibah di Iran - Fauzinudin, Muhammad (ULUL ALBAB Jurnal Studi Islam, 2017)
This article aims to analyze the extent to which the Iranian state, which is predominantly Shiite Muslims contribute in reforming the Islamic legal system, especially on inheritance by right and inheritance by will (wajibah). Both are interestingly studied because in the study of jurisprudence this term is a very fundamental topic (religious affairs involving others). Since this study is only a study of texts, the approach taken is to look at some of the chapter in the laws relating to inheritance prevailing in Iran and to relate them to the majority of schools there. This article concludes that in the Iranian shrimp system, a wife will get all the inheritance of her husband, not just half of heritage. She also obtained to get her husband's land that was previously banned in the old law. The cause of renewal of inheritance law in Iran state can not be separated from some aspects, covering normative and socio-political aspects as well as social reality, including the turbulence of difference of schools. All material of inheritance law and family is based on Shi'ah Itsna ‘Asyariyah (Ja‘fari) family law.